Enhancing the permeability and anti-fouling properties of a polyamide thin-film composite reverse osmosis membrane via surface grafting of l-lysine. Issue 35 (27th June 2019) - Liu, Tianyu; Chen, Dandan; Yang, Feng; Chen, Jinyao; Cao, Ya; Xiang, Ming; Kang, Jian; Xu, Ruizhang
Abstract : Hydrophilicity is improved without altering the original morphology and thickness of RO membranes after modification. Abstract : The application of a reverse osmosis (RO) membrane is greatly restricted on account of a trade-off between water flux and salt rejection, as well as poor anti-fouling properties. In order to improve the surface hydrophilicity of RO membranes, l -lysine (Lys) was grafted onto polyamide selective layers with the premise of maintaining the original surface morphology and thickness, which were verified through scanning electron microscopy and atomic force microscopy analysis. X-ray photoelectron spectroscopic measurements confirmed the occurrence of the reaction. After modification, the RO membranes exhibited notably enhanced hydrophilicity due to a steep decline in their water contact angles. The results of cross-flow filtration tests manifested that the modified membranes showed evident enhancements in water flux and salt rejection. For the optimized samples, the water flux increased by 22.45% compared with the pristine membrane, and the salt rejection rose up to 98.53% from the initial value of 95.44%. After grafting, the RO membranes performed much better in fouling resistance, especially towards protein and cationic foulants. The mechanism of how grafted Lys affected the performance of the RO membranes was analyzed. This research provides a feasible method to optimize the performance of RO membranes.